The Translation of Pronouns and Repetitions in Indonesian Children’s Story "Petualangan Si Kancil" into French Using Google Translate - Sajarwa Sajarwa; Muhammad Yunus; Reny Nur Rohmah; Cecile Elisabeth Marie Bellat (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. There are many things to consider in translating children’s stories: behavioral influence on children, level of language difficulty, and suitability to the target culture. A child has limitations in their social interactions and communications. This article analyzes the translation of pronouns and repetitions in a children’s story with Google Translate. As an online application, Google Translate is considered to have the ability to translate words, phrases, clauses, sentences, and even paragraphs. This study aims to reveal the ability of google translate to translate children's stories, especially Indonesian pronouns and repetitions into French. This study used data from the translation of an Indonesian children's story titled “Petualangan Si Kancil” (literal translation: “The Adventures of the Mouse Deer”) by means of Google Translate, adopting descriptive and comparative methods. The results of data analysis show that Google Translate only translates word for word or sentence for sentence, and has not considered the cultural context. In detail, the results are as follow: (i) pronoun translation cannot sufficiently reflect both the writing style and the cultural context of the source text, (ii) translation of repetitions is avoided and replaced with lexical equivalence.Keywords: Children’s Story; Google Translate; Pronouns; Repetitions